Building product ontology: Core ontology for Linked Building Product Data - Wagner, Anna; Sprenger, Wendelin; Maurer, Christoph; Kuhn, Tilmann E.; Rüppel, Uwe (Automation in construction, 2022)
•Linked Building Product Data applied Linked Data to define building products.•Modular and flexible approach for individual configurations.•Building Product Ontology serves as a core structure of all configurations.•Uniform querying and reasoning possible. The digitalisation of the Architecture, Engineering and Construction domain introduced new methods for digital collaboration, i.e. Building Information Modelling (BIM). While this method focuses on building data, the distribution of digital product models is still problematic, complicating uniform product searches and automated product data processing. Existing schemas, such as a subpart of the Industry Foundation Classes or the German VDI 3805, rely on rigid or template-driven schemas, that do not support the description of innovative or multi-functional products or impose a large schema overhead and complexity on manufacturers. Therefore, this article combines flexible and modular product descriptions with Semantic Web technologies and Linked Data. By applying Web-based technologies, the searchability of product data and the applicability of distributed data are expected to be enhanced. More precisely, this article proposes a concept for Linked Building Product Data and introduces the generic Building Product Ontology as a potential core schema of the concept. To demonstrate the feasibility of Linked Building Product Data and the Building Product Ontology, the authors apply both the concept and the data schema to innovative and multi-functional example products that cannot be described with the existing approaches for product descriptions. The evaluation demonstrates the flexibility, modularity and overall suitability of the presented concepts, meeting all collected requirements for digital product descriptions. Hence, Linked Building Product Data may solve existing issues with rigid product description schemas. At the same time, this approach complements the current research trend of Linked Building Data.